Peningkatan pengetahuan kader posyandu dalam penanganan luka dan pencegahan infeksi di Puskesmas Taman Bacaan kota Palembang - Veny Larasati; Zen Hafy; Soilia Fertilita; Riana Sari Puspita Rasyid; Ajeng Intan Estri Amanda (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Community empowerment is a strategic step to improve quality of life by increasing individual and community capacity, particularly in the health sector. Integrated service post (Pos Pelayanan Terpadu / Posyandu) cadres at the Taman Bacaan Community Health Center in Palembang City face challenges in recognizing wound types, prioritizing initial treatment, performing proper wound cleansing techniques, applying infection prevention principles, and determining the appropriate time to refer patients to health facilities. This situation highlights the need for educational interventions and community-based practical training to improve the capacity of cadres to provide safe and appropriate first aid. The goal of this integrated health post (Posyandu) cadre empowerment program is to improve their capacity in treating minor injuries and preventing infections in the community. The activity was conducted on October 25, 2025, with 54 cadres participating. Pre-tests and post-tests served as the evaluation instruments. The results were analyzed using descriptive analysis of the cadres' demographics and an analysis of their knowledge (based on pre-test and post-test scores). The analysis indicates a consistent increase in knowledge among all participants. The average pre-test score was 5.55, while the average post-test score was 8.11. This represents an increase of 2.56 points—or 46.1%—from the baseline, demonstrating that knowledge improved following the training. These findings are reinforced by the positive delta scores observed across all participants, confirming that the training had a consistent impact on cadres regardless of their educational background, age, or length of experience.